Effect of cesium and cerium substitution on the dielectric properties of CaCu 3Ti 4O 12 ceramics - Makcharoen W. (2017)
In this study, CaCu 3 Ti 4 O 12 (CCTO) ceramics were doped with cesium and cerium atoms to possibly improve the electrical properties of these widely used ceramics. In all cases, pure phase perovskites were produced where cesium doping enhanced the grain growth and cerium doping produced grain growth inhibition. The cesium doping showed an improvement in loss tangent performance, in contrast to the cerium doping which showed a negative result. A high dielectric constant > 15,000 with a dielectric loss lower than 0.06 was observed for cesium 2.0 mol% doped at high frequencies. These results were related to the change in microstructure and the properties of grain boundary after doping. © 2011 Elsevier Ltd and Techna Group S.r.l.